Side Business Contributions (Trigona Bee Farming) and The Main Business for Household Income - Abdillah, Al Hibnu; Barkani, Barkani; Juraemi, Juraemi (Universitas Djuanda, 2024)
Trigona bee farming business as a side business for members of the Tribona Reborn farmer group as an effort to increase family household income, until now it is not known how much the value of its contribution to household income is. The aim of this study was to see how much the contribution of the main and side business income of Trigona sp. honey bee farming. to the household income of the Trigona Reborn farmer group. The research was carried out from June to August 2021 in South Sangatta Village. Sampling using saturated sampling. The data analysis method used is descriptive quantitative using the income analysis formula, the level of profit and income contribution. The total income of Trigona sp. as much as Rp. 103,042,600, with an average of Rp. 9,367,509. The percentage of revenue contribution from Trigona sp.'s side business, main income, and other side income is 8.7% (low); 80.1% (high); and 11.2% (low). Even though it makes a low contribution to total income, it can be an alternative as an additional business and fill free time for breeders in between their daily activities. It is hoped that the side business of Trigona sp. continues to grow, to help contribute to the family income of farmer group members.